2022
DOI: 10.1101/2022.08.05.503007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rates but not acoustic features of ultrasonic vocalizations are related to non-vocal behaviors in mouse pups

Abstract: Mouse pups produce ultrasonic vocalizations (USVs) in response to isolation from the nest (i.e., isolation USVs). Rates and acoustic features of isolation USVs change dramatically over the first two weeks of life, and there is also substantial variability in the rates and acoustic features of isolation USVs at a given postnatal age. The factors that contribute to within-age variability in isolation USVs remain largely unknown. Here, we explore the extent to which non-vocal behaviors of mouse pups relate to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 89 publications
0
0
0
Order By: Relevance
“…The dynamic nature of call features may depend on physiological factors such as fatigue and emotional factors such as stress. Regulation of USV call emission, is tightly related to pup breathing (Portfors, 2007;Wei et al, 2022) and its "arousal state" (Rieger and Dougherty, 2016;Pranic et al, 2022). It was suggested that the temporal variables such as duration and ICI are associated with motor control by central generators of breathing rhythm, while the spectral properties of the calls are dictated by the laryngeal structures with several laryngeal elements involved in voice production and its spectral properties (such as the ventral pouch; Riede et al, 2017Riede et al, , 2020Abhirami et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic nature of call features may depend on physiological factors such as fatigue and emotional factors such as stress. Regulation of USV call emission, is tightly related to pup breathing (Portfors, 2007;Wei et al, 2022) and its "arousal state" (Rieger and Dougherty, 2016;Pranic et al, 2022). It was suggested that the temporal variables such as duration and ICI are associated with motor control by central generators of breathing rhythm, while the spectral properties of the calls are dictated by the laryngeal structures with several laryngeal elements involved in voice production and its spectral properties (such as the ventral pouch; Riede et al, 2017Riede et al, , 2020Abhirami et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the CPF and MTHFR models, the pups in this developmental model had no postnatal sensorimotor deficits and no abnormalities of vocal fold structure. Arousal state and stress are possible modulators of pup response (Pranic et al, 2022).…”
Section: Discussionmentioning
confidence: 99%